2003
DOI: 10.1068/p5128
|View full text |Cite
|
Sign up to set email alerts
|

Gaze Stability of Observers Watching Op Art Pictures

Abstract: It has been the matter of some debate why we can experience vivid dynamic illusions when looking at static pictures composed from simple black and white patterns. The impression of illusory motion is particularly strong when viewing some of the works of 'Op Artists, such as Bridget Riley's painting Fall. Explanations of the illusory motion have ranged from retinal to cortical mechanisms, and an important role has been attributed to eye movements. To assess the possible contribution of eye movements to the illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
48
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 21 publications
6
48
0
Order By: Relevance
“…Our results directly confirm the hypothesis proposed by Pritchard (15), Mon-Williams and Wann (17), and Zanker and colleagues (18)(19)(20) that small eye movements can drive the perception of illusory motion in Enigma and other static patterns. Thus, our findings are compatible with a causal relationship between microsaccade rates and the perception of illusory motion.…”
Section: Effect Of Microsaccades In the Perception Of Illusory Motionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our results directly confirm the hypothesis proposed by Pritchard (15), Mon-Williams and Wann (17), and Zanker and colleagues (18)(19)(20) that small eye movements can drive the perception of illusory motion in Enigma and other static patterns. Thus, our findings are compatible with a causal relationship between microsaccade rates and the perception of illusory motion.…”
Section: Effect Of Microsaccades In the Perception Of Illusory Motionsupporting
confidence: 81%
“…The third potential explanation of illusory motion in static repetitive patterns came from Pritchard (15), who proposed that the illusion might be due to changes in retinal stimulation produced by small eye movements. This proposal was supported by Evans and Marsden (16), Mon-Williams and Wann (17), and Zanker and colleagues (18)(19)(20), who investigated another op-art painting giving rise to illusory motion effects: Fall, by Bridget Riley (Fig. S1B).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Usually, the experience of viewing this painting is described in terms of introspection, with labels like 'shimmer', 'flicker', or 'waves of movement'; or in a more specific way as a pattern of horizontal, not clearly delineated bands in which gratings seem to move in one coherent but random and often changing direction, and different directions within each band. To assess the conditions for seeing the dynamic illusions (Zanker et al 2003), observers were asked to rate the strength of the illusion perceived in a number of stimuli on a scale between 1 (completely static) and 5 (moving vividly). In an initial experiment the expectation was confirmed that the strength of the illusion varies with the modulation amplitude of the riloid (i.e.…”
Section: An Experimental Analysismentioning
confidence: 99%
“…It is clear from these data that the illusion virtually disappeared when the retinal image of the pattern was stabilised, while ratings close to maximum Fig. 1 Riloids -synthetic Op art patterns -can be generated according to a simple mathematical expression (see Zanker et al 2003;Zanker 2004) by sinusoidal modulation of intensity with a grating period, l, and a phase modulation of amplitude A and modulation period m that can vary along the vertical dimension. Resulting grey-level bitmaps of wiggly line patterns resemble Riley's 'Fall' (Riley 1999), and were therefore dubbed 'riloids'.…”
Section: An Experimental Analysismentioning
confidence: 99%